Vocabulario de la lengua Tagala - Noceda, Juan José de, 1681-1747; Sanlucar, Pedro de, 1707-; Almario, Virgilio S.; Ebreo, Elvin R.; Yglopaz, Anna Maria M.; Philippines. Komisyon sa Wikang Filipino (Maynila : Komisyon sa Wikang Filipino, 2013)
Tagalog-Spanish and Spanish-Tagalog dictionary.
Originally published: Manila : Imprenta de Ramirez y Giraudier, 1860.
Spanish and Tagalog.
Keywords: Tagalog language -- Dictionaries -- Spanish; Spanish language -- Dictionaries -- Tagalog